MANAGEMENT OF ORBITAL FLOOR FRACTURE WITH AUTOCLAVED X-RAY FILM: Management of Orbital Floor Fracture - Shoaib, Col Khawaja Khalid; Haq, Inam-ul-; Ali, Kashif; Mukhtar, Muhammad Ahsan (Pakistan Armed Forces Medical Journal, 2008)
.